Medical Students’ Knowledge, Attitude, Practice, and Perceived Barriers Towards Medical Research: A Cross-Sectional Study - Ahmed A. Mosa; Ali Jotiar Mahmood; Kani F. Farooq; Jodi R. Haji; Dana Jacksi; Daliya K. Mohamed-Saqid; Talar R. Mnasakan (Galician Medical Journal, 2023)
Background. Medical research and innovation are essential for the growth of medical education and healthcare system. Medical students should be taught in a research-informed environment, which allows them to make better clinical decisions and enhances their scientific output.